2015
DOI: 10.1155/2015/634252
|View full text |Cite
|
Sign up to set email alerts
|

A Complicated Case of Acute Promyelocytic Leukemia in the Second Trimester of Pregnancy Successfully Treated with All-trans-Retinoic Acid

Abstract: A 40-year-old female at 26-week gestation was diagnosed with acute promyelocytic leukemia (APL) after an abnormal prenatal lab workup showed pancytopenia. She was treated with all-trans-retinoic acid (ATRA), idarubicin, and dexamethasone. After day one of treatment, she developed differentiation syndrome, which was treated with dexamethasone. At 30-week gestation, she had preterm premature rupture of membranes and delivered by cesarean section because of the fetus' breech presentation. Despite ATRA's potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…[4] Coagulation abnormalities, disseminated intravascular coagulation, placental abnormalities, premature delivery, and obstetric complications may be observed at presentation or during the course of disease. [5][6][7] Urgent and competent management with ATRA may ameliorate coagulation parameters and bleeding, as in our patient.…”
Section: Discussionsupporting
confidence: 52%
“…[4] Coagulation abnormalities, disseminated intravascular coagulation, placental abnormalities, premature delivery, and obstetric complications may be observed at presentation or during the course of disease. [5][6][7] Urgent and competent management with ATRA may ameliorate coagulation parameters and bleeding, as in our patient.…”
Section: Discussionsupporting
confidence: 52%
“…In our case, there was no teratogenic risk since the treatment began after the organogenesis period (4-10 WG). Many cases of pregnancies with ATRA during the second and third trimesters are reported in the literature with no serious adverse outcomes [6,[9][10][11].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the guarded prognosis, prompt ICU admission and the multidisciplinary team approach positively impacted the overall patient outcome. Some but not all reviewed cases reported mild differentiation syndrome [ 8 , 12 , 13 ]. In Santolaria’s review, the causes of death were reported in 7 patients (out of a total of 10 deaths): 3 intracranial hemorrhages, 3 cases of multiorgan failure (2 caused by severe differentiation syndrome), and 1 caused by infection [ 8 ].…”
Section: Discussionmentioning
confidence: 99%